2014
DOI: 10.1111/jfpp.12273
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination and Sensory Properties of Microbiologically Contaminated Fresh Fruits and Vegetables by Microwave Plasma Processed Air (PPA)

Abstract: Currently used disinfection or sanitation methods for fresh fruits and vegetables lack antimicrobial effectiveness, but are high in costs, water consumption or chemicals. One alternative could be to apply nonthermal plasma at atmospheric pressure to the described issue. The experimental set-up implements microwave plasma, which generates plasma processed air (PPA) containing manifold reactive nitrogen species-based chemical and antimicrobial compounds. Five different fresh produces were first contaminated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 41 publications
4
45
1
1
Order By: Relevance
“…Schnabel et al (2014) analyzed the composition of microwave PPA using identical experimental conditions via mass spectrometry and showed that 2.7% of the working gas is converted into NO 2 , NO, and a mixture of HNO 2 , HNO 3 , CO 2 , and H 2 O. As nitric oxide (NO) cannot coexist with ozone or atomic oxygen the formation of O 2 , NO 2 and NO 3 proceeds via oxidation reactions (Surowsky, Schlüter, & Knorr, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schnabel et al (2014) analyzed the composition of microwave PPA using identical experimental conditions via mass spectrometry and showed that 2.7% of the working gas is converted into NO 2 , NO, and a mixture of HNO 2 , HNO 3 , CO 2 , and H 2 O. As nitric oxide (NO) cannot coexist with ozone or atomic oxygen the formation of O 2 , NO 2 and NO 3 proceeds via oxidation reactions (Surowsky, Schlüter, & Knorr, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The use of microwave-driven plasma torches is a wellestablished technique to generate plasma and has attracted the interest of a range of scientists in recent years because of its unique advantages (Baier, Herppich, Ehlbeck, Knorr, & Schlüter, 2015;Hertwig, Reineke, Ehlbeck, Knorr, & Schlüter, 2015;Schnabel, Niquet, Schlüter, Gniffke, & Ehlbeck, 2014). In this work, an evaluation of the potential use of PPA for the inactivation of PPO and POD in fresh cut and subsequently freeze and warm air dried produce from apple and potato tuber was conducted.…”
Section: Introductionmentioning
confidence: 98%
“…At the same time, essential food characteristics remain untouched. Plasmas are also active against microorganisms that are sometimes pathogenic or putrefy food as has been shown in fish, meat, poultry, cheese, fruits, vegetables, seeds, eggs, dried nuts, dried milk, and spores in spices . Also, an inactivation of Escherichia coli , Salmonella spp ., Vibrio parahaemolyticus , Listeria monocytogenes , Staphylococcus aureus , Bacillus cereus , and foodborne viruses in different foods could be demonstrated .…”
Section: Decontamination Of Surfaces and Liquidsmentioning
confidence: 99%
“…Shama and Kong (2012) published a summary on plasma decontamination of foods, including bacon, pork, ham, apples, melons, mangos, lettuce, cheese, eggs and nuts. Furthermore, there have been recent studies on plasma treatment of corn salad (Baier et al, 2013), fresh fruits and vegetables (Schnabel et al, 2014), whole black pepper , and herbs and spices (Hertwig et al). Escherichia coli on almonds was inactivated by applying plasma (Deng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%